Efficiency of Therapeutic Plasma-Exchange in Acute Interstitial Lung Disease, Associated With Polymyositis/Dermatomyositis Resistant to Glucocorticoids and Immunosuppressive Drugs: A Retrospective Study - Ning, Yaogui; Yang, Guomei; Sun, Yuechi; Chen, Shiju; Liu, Yuan; Shi, Guixiu (Frontiers in Medicine, 2019)
Interstitial lung disease (ILD) is a life-threating complication, commonly associated with polymyositis (PM), and dermatomyositis (DM). A subset of acute ILD associated with PM/DM patients are refractory to conventional treatment, and leads to a high rate of mortality. The efficacy of therapeutic plasma-exchange (TPE) as a PM/DM treatment to improve muscle involvement is controversial due to a lack of evidence. However, in recent reports, TPE has been effective in improving lung involvement. To evaluate the efficacy of this therapy, we retrospectively studied TPE treatment outcomes for in 18 acute PM/DM-ILD patients who were resistant to conventional therapies. Five patients were diagnosed with DM (27.8%), 11 with CADM (61.1%), and two with PM (11.1%). Among 18 patients, 11 (61.1%) achieved satisfactory improvement after four or more rounds of TPE, whereas seven died due to respiratory failure. We also analyzed risk factors to predict unresponsiveness to TPE in these patients. Notably, the prevalence of subcutaneous/mediastinal emphysema was significantly higher in the non-responsive group (6/7, 85.7%) than in the responsive group (2/11, 18.2%; P = 0.013); moreover, patients with this complication were mainly in the CADM subgroup (6/8, 75%). Subcutaneous/mediastinal emphysema and increased serum ferritin levels were shown to be poor prognostic factors, predictive of unresponsiveness to TPE, in PM/DM patients. No autoantibodies were found to be associated with TPE outcome, although we only investigated anti-Jo-1 and anti-Ro antibodies; the clinical significance of other myositis-specific autoantibodies, especially anti-melanoma differentiation-associated gene 5 (MDA5) antibody, is not known. Our results indicate that TPE might be an alternative treatment for acute PM/DM-ILD patients resistant to conventional therapies, except for those with subcutaneous/mediastinal emphysema and high serum ferritin levels.